Hydrogeology of the Quaternary unit at Ali Al-Gharbidistrictnortheast Missan Governorate, Iraq - Alaa M. Al-Abadi1and Fadhil K. Jabbar2Ahmed M.Hashoosh¹, ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Management of groundwater resources requires a comprehensive understanding of the ‎hydrogeological characteristics of the water-bearing layers. Although, the importance of ‎groundwater resources in the northeastern Missangovernorate, south of Iraq for growing ‎agricultural activities and industrial purposes, there is no study so far to build the conceptual model ‎of the aquifer system and estimate its hydraulic characteristics. This study aims to use the available ‎well log records, field data and pumping test data to study the hydrogeological characteristics of the ‎aquifer system in the Quaternary units which mainly consists of sand and gravel in addition to clay ‎and silt. Several cross-sections were drawn based on the well logs and analysis of these cross-‎sections proved that the aquifer system in the Quaternary water-bearing layer is a single shallow ‎unconfined aquifer with an average saturated thickness equals 42 m. The aquifer in the study area is ‎mainly recharged by rainfall and the groundwater flow is from the northeast to southwest. ‎Monitoring of groundwater level in thirty wells for six months indicated the groundwater level slightly ‎fluctuates means that there is a balance between the applied stress on the aquifer system (recharge ‎and discharge). Analysis of pumping test data in six wells showed that the hydraulic conductivity ‎ranges 1.10 – 10.41 m/d, the transmissivity is between 34.01 to 426.9 m2/d, and the specific yield is ‎between 0.01 to 0.12. The storage in stock and renewable storage were (3*10⁹m³,1*10⁹mᵌ), respectively. Wise management of the aquifer system is urgent to prevent the minimizing of the resource and ‎deterioration of its quality.